APLIKASI WHATSAPP SEBAGAI MEDIA ALTERNATIF UJIAN ONLINE DI SIT MUSH’AB BIN UMAIR - Barlian, Taufik; Roni, Kiagus Ahmad; Sofiah, Sofiah; Apriani, Yosi (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Distance learning causes teachers to think creatively so that the teaching and learning process continues as it should. In addition, various platforms and media for online learning are still not widely known by teachers. The Whatsapp application is an application that is already widely used. In this application, it is possible to form groups that can gather many people to be able to chat with each other and exchange information that allows the delivery of messages in groups besides delivering messages individually. The purpose of this service is so that teachers can make maximum use of the Whatsapp media as a distance learning facility. The method in this service of AbdiMas team took the initiative to conduct a one day coaching clinic using the Whatsapp application as a means of evaluating student learning to SIT Mush'ab bin Umair teachers. The conclusion of this dedication activity is that this community service activity is felt to be very beneficial for the SIT Mush'ab bin Umair teachers. In part, the limitations of online learning facilities and infrastructure can be overcome by using Whatsapp. The use of Whatsapp as an online exam means is considered relatively cheap with a wide reach, easy to use, especially for most of the students of SIT Mush'ab bin Umair who are still in grades 1 and 2.